Revisiting "crimes of the powerful": Marxism, crime and deviance - Bittle, Steven (Crimes of the powerful, 2018)
Theoretical and conceptual excursions -- Conceptualisation, theoretical practice and crimes of the powerful / Jon Frauley -- Law : ideological whitewashing and positive enabling of coercion / Harry Glasbeek -- Underworld as servant and smokescreen : crimes of the powerful and the evolution of organized crime control / Michael Woodiwiss -- Shadow boxing against the crimes of the powerful / Margaret Beare -- Between force and consensus / Vincenzo Ruggiero -- Developing pearce's new materialism / Nick Hardy -- "Expropriative" sacrifice and zombie capitalism : a radical Durkheimian approach / Ronjon Paul Datta -- Power, crime and enclosure : capital accumulation in the twilight of the neoliberal SSA / Raymond Michalowski -- Crimes of the powerful research : empirical dimensions -- Marx reloaded for the 21st century : capitalism, agency and the crimes of the powerful / Kristian Lasslett -- The imaginary social order of corporate criminal liability / Liisa Lähteenmäki and Anne Alvesalo-Kuusi -- Global capital, the rigging of interbank interest rates, and the capitalist state / Gregg Barak -- Pipelines, presidents and people power : resisting state-corporate environmental crime / Elizabeth A. Bradshaw -- Pesticeland : Brazil's poison market / Stéfanie Khoury -- No criminology of wage theft : revisiting "workplace theft" to expose capitalist exploitation / Paul Leighton -- Prying into the pockets of public figures / Scott Poynting -- Crimes of the powerful and the spanish crisis / Ignasi Bernat -- Crimes of globalization and Asian dam projects : powerful institutions and slow violence / David O. Friedrichs -- New developments in crimes of the powerful research -- An extension of frank pearce's work on crimes of the powerful : "demystification" and the role of our consent / Dawn I. Rothe and Victoria E. Collins -- Debtfarism, predatory lending and imaginary social orders : the case of the US payday lending industry / Susanne Soederberg -- Failure to protect : state obligations to victims and state crime / Laura Finley -- "Punitive reformation" : state-sanctioned labour through criminal justice and welfare / Jon Burnett -- Imperialism : the general theory of crimes of the powerful / Biko Agozino -- Frank pearce and colonial state crimes : contributions to a research agenda / Jose Atiles -- Organized irresponsibility, corporations, and the contradictions of collective agency and individual culpability / Dean Curran